The Middle East and Brazil : perspectives on the new global south - Amar, Paul (Paul Edouard), 1968- (Bloomington : Indiana University Press, 2014)
"With its new political and cultural affiliations with the Middle East and the renewed visibility of the country's millions of practicing Muslims and those with Middle Eastern roots, Brazil may offer valuable lessons for countries transformed by the "Arab Spring." This groundbreaking collection reveals the historical links between these two world regions, describes the emergence of new South-South solidarities, and offers new methodologies for the study of transnationalism, global culture, and international relations"--
The Middle East and Brazil : transregional politics in the Dilma Rousseff era / Paul Amar -- The summit of South America-Arab States : historical contexts of South-South solidarity and exchange / Paulo Daniel Elias Farah -- Brazil's Relations with the Middle East in the "oil shock" era : pragmatism, universalism, and developmentalism in the 1970s / Carlos Ribeiro Santana -- Palestine-Israel controversies in the 1970s and the birth of Brazilian transregionalism / Monique Sochaczewski -- Terrorist frontier cell or cosmopolitan commercial hub? : the Arab and Muslim presence at the border of Paraguay, Brazil, and Argentina / Fernando Rabossi -- Tropical Orientalism : Brazil's race debates and the Sephardi-Moorish Atlantic / Ella Shohat and Robert Stam -- Slave barracks aristocrats : Islam and the Orient in the work of Gilberto Freyre / Alexandra Isfahani-Hammond -- Islamic transnationalism and anti-slavery movements : the Male Rebellion as debated by Brazil's press, 1835-1838 / Jose T. Cairus -- A transnational intellectual sphere : Brazil and Its Middle Eastern populations / Maria del Mar Logrono Narbona -- The politics of anti-Zionism and racial democracy in homeland tourism / John Tofik Karam -- Rio de Janeiro's global bazaar : Syrian, Lebanese, and Chinese merchants in the Saara / Neiva Vieira da Cunha and Pedro Paulo Thiago de Mello -- Muslim identities in Brazil : engaging local and transnational spheres / Paulo Gabriel Hilu da Rocha Pinto -- Telenovelas and Muslim identities in Brazil / Silvia M. Montenegro -- Turco peddlers, Brazilian plantationists, and transnational Arabs : the genre triangle of Levantine-Brazilian literature / Silvia C. Ferreira -- Multiple homelands : heritage and migrancy in Brazilian Mahjari literature Armando Vargas -- Orientalism in Milton Hatoum's fiction / Daniela Birman -- Arab-Brazilian literature : Alberto Mussa's Mu[AYN]allaqa and South-South dialogue / Wail S. Hassan.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Muslims -- Brazil -- History; Muslims -- Brazil -- Ethnic identity; Transnationalism -- Social aspects -- Brazil; Transnationalism -- Political aspects -- Brazil; Transnationalism in literature; Brazilian literature -- History and criticism; Middle East -- Relations -- Brazil; Brazil -- Relations -- Middle East; Brazil -- Ethnic relations -- History; Electronic books